Association between positive murine double minute 2 expression and clinicopathological characteristics of esophageal squamous cell carcinoma: a meta-analysis. Issue 7 (1st October 2016) - Chen, J. Y.; Yang, H.; Wen, J.; Luo, K. J.; Liu, Q. W.; Lei, J. Y.; Zhen, Y. Z.; Fu, J. H.
Summary: The correlations of murine double minute 2 (MDM2) T309G and esophageal cancer were elucidated because the association between MDM2 expression states and clinicopathological parameters of esophageal squamous cell carcinoma (ESCC) is controversial. We conducted a meta-analysis on studies screened from PubMed, Web of Science, Embase, the Cochrane Library, and the Chinese Biomedical Literature Databases that were published before October 2014. All studies describing the association between MDM2 and ESCC were traced. Meta-analysis was performed using the STATA software (Stata Corp., College Station, TX, USA). A total of 9 studies with 707 cases and 324 controls were included. MDM2 expression was higher in ESCC than in normal esophageal epithelium (odds ratio [OR] 10.38, 95% confidence interval [CI] 6.42–16.78, P < 0.001). High MDM2 expression was associated with early primary tumor stage (T1/T2 vs. T3/T4, OR 0.59, 95% CI 0.38–0.92, P = 0.018) and increased risk of regional lymph node metastasis (N0 vs. N1, OR 1.66, 95% CI 1.03–2.67, P = 0.039). However, no relationship was observed between MDM2 expression and the risk of distant metastasis (OR = 2.09, 95% CI 1.00–4.36, P = 0.050), and MDM2 was not significantly correlated with TP53 expression (OR 1.22, 95% CI 0.53–2.77, P = 0.643). Our analysis suggests that MDM2 acts as a potent marker of early primary tumor stage but higher risk of regional lymph node metastasis in ESCC. However, because of the limited number of studies included, the result should be further clarified by well-designed prospective studies.